2016
DOI: 10.21037/jtd.2016.03.46
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of helical intensity-modulated radiotherapy for stage III non-small cell lung cancer in comparison with conventionally fractionated 3D-CRT

Abstract: Background:The standard treatment for stage III non-small-cell lung cancer (NSCLC) is still 60 Gy in conventional fractions combined with concurrent chemotherapy; however, the resulting local controls are disappointing. The aim of this study was to compare and assess the feasibility and efficacy of hypofractionated chemoradiotherapy using helical tomotherapy (HT) with conventional fractionation as opposed to using three-dimensional conformal radiotherapy (3D-CRT) for stage III NSCLC. Methods: Sixty-nine patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Treatment planning, including radiation targets, normal tissue dose constraints, and delivery techniques for locally advanced NSCLC in our institution have been previously described [8]. The fractionation regimes primarily depended on the treating physicians’ preference, based on the clinical tumor size and location.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment planning, including radiation targets, normal tissue dose constraints, and delivery techniques for locally advanced NSCLC in our institution have been previously described [8]. The fractionation regimes primarily depended on the treating physicians’ preference, based on the clinical tumor size and location.…”
Section: Methodsmentioning
confidence: 99%
“…e institutional dosimetry constraints for normal organs at risk (lungs, heart, esophagus, and spinal cord) were previously described in detail [15]. e following RT schemes were implemented: (1) 60 Gy/20 fractions (3.0 Gy/fraction, BED � 78 Gy, commonly used for peripheral tumors); (2) 62.…”
Section: Treatmentmentioning
confidence: 99%
“…In 2013, Oh et al reported that chemotherapy concurrent with radiotherapy (2.4 Gy/f) can achieve a median survival time of 27.3 months [ 11 ]. In 2016, He et al reported a median survival time of 31.6 months with the use of tomotherapy (60 Gy/20f) in patients with stage III NSCLC; the 1-year and 2-year survival rates were 88.2% and 58.1%, respectively [ 12 ]. In a study by Walraven et al, high-dose radiotherapy (66 Gy/24f) with cisplatin was found to prolong the median survival time to 31.5 months; the 1-year and 5-year survival rates were 74.5% and 37.3%, respectively [ 13 ].…”
Section: Discussionmentioning
confidence: 99%